Influence of genetic factors of humans, mosquitoes and parasites, on the evolution of Plasmodium falciparum infections, malaria transmission and genetic control methods: a review of the literature - Seni Nikiema; Issiaka Soulama; Gifty Dufie Ampofo; Moustapha Nikiema; Abdou Azaque Zouré; Salif Sombié; Salam Sawadogo; Nicolas Ouedraogo; Samuel Sindie Sermé; Haffsatou Sawadogo; Raïssa Ily; Guillène Y. N. Tibiri; et al. (BMC Medical Genomics)
Abstract Despite significant progress, malaria remains a public health problem in many regions, particularly in sub-Saharan Africa. This situation is partly explained by the mosquito’s resistance to insecticides and the emergence of parasite resistance to antimalarial drugs. Indeed, in spite of the various vectors’ controls, insecticide resistance emerges from multi-generational selection and poses worldwide concern. In parallel, artemisinin resistance unfortunately emerged independently in multiple countries in eastern Africa. Since 2014, artemisinin resistance has been observed in 6 countries in Africa and, more concerningly, the evidence from longitudinal molecular surveys in these countries suggests that it is spreading. While phenotypic evidence of treatment failure is still limited, the increasing reports of validated artemisinin resistance mutations are alarming. Unlike the emergence of artemisinin resistance in South-East Asia, our understanding of the genetic determinants of artemisinin resistance and our ability to sequence and map the spread of resistance are significantly greater. In addition to mosquito and parasite genetics affecting malaria evolution, many human individual variants have been identified that are associated with malaria protection, but the most important of all relates to the structure or function of red blood cells, the classical polymorphisms that causes sickle cell trait, α-thalassaemia, G6PD deficiency, and the major red cell blood group variants. In that biological complex context, there is a need to characterize the various genetic factors in Plasmodium falciparum, humans and mosquitoes that are potentially associated with resistance to antimalarial drugs and insecticides, and their involvement in the evolution, severity and transmission of malaria. In this direction, A comprehensive literature review was conducted to capture the objectives highlighted above. The advances in genomic surveillance and emerging genetic control strategies, such as gene drive technology were also considered in this review. We used search engines such as PubMed and Google scholar to retrieve articles useful to the objective of this paper and information on the knowledge of genetic factors and methods that contributed to malaria control were synthesized.